Pronunciation - Laroy, Clement; Maley, Alan. (Oxford : New York : Oxford University Press., 2005)
This very popular series gives teachers practical advice and guidance, together with resource ideas and materials for the classroom.
Includes bibliographical references and index.
Keywords: English language -- Pronunciation -- Study and teaching (Elementary); English language. -- Pronunciation -- Study and teaching (Elementary); Activity programs. -- Activity programs -- English language -- Study and teaching -- Pronunciation